PEMANFAATAN TUNGKU BERBAHAN BAKAR LPG DAN MODIFIKASI RUANG BAKAR UNTUK PEMBAKARAN KERAMIK UKIR BERGLASIR - M. Dachyar Effendi (Jurnal Energi dan Lingkungan (Enerlink), 2010)
A downdraft kiln using LPG as energy source with capacity 1 m3 and maximumfiring temperature 13000C has been constructed and midified to give better heatdistribution. For firing ceramic process, most of Balinese and Lombok craftsmenuse firewood as energy source. This method is inefficient from the production rate.Point of view, downdraft kiln can help the craftsmen to process ceramic easier,faster and cheaper. Downdraft kiln using LPG has been selected as an alternativekiln due to minimum pollutant produced compare with updraft kiln using coal orfirewood. The kiln constructed has fulfilled the requirement of kiln firing processquality in which the firing causes sintering process in the ceramics body. The kilnwith a capacity of 1m3 can reach a maximum firing temperature which of 13000C.To test this modified kiln, some carved ceramic has burned into the kiln. Carvedceramic has been chosen caused by need more good heat distribution than otherceramic design product and have differ thickennes in all bodies.The final productgive a better product whithout defect compare to product burned into unmodifiedkilnKata kunci: tungku hemat energi, keramik ukir, stoneware